Interactivity to enhance perception: Does increased interactivity in mobile visual presentation tools facilitate more accurate rating of textile properties? - Orzechowski, P.; Atkinson, Doug; Padilla, S.; Methven, T.; Baurley, S.; Chantler, M. (2011)
As part of the EPSRC funded 'Digital Sensoria' project a set of digital tools were utilised to better demonstrate the tactile qualities of textiles via the internet. Shoogleit [8], an online utility for the creation of interactive video was one such tool. A Shoogle player for iOS mobile devices was then created (Orzechowski) using an iterative process, during which experiments were carried out to determine if the added interactivity afforded by Shoogleit could more accurately describe textile qualities and thus aid in the creation of a next generation mobile browser for textiles.